2001
DOI: 10.1021/jf001071k
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Specific Detection of Hydroxyl Radical Using an Ultraweak Chemiluminescence Analyzer and a Low-Level Chemiluminescence Emitter:  Application to Hydroxyl Radical-Scavenging Ability of Aqueous Extracts of Food Constituents

Abstract: With the availability of an ultraweak chemiluminescence analyzer, it is possible to monitor the production of a specific oxygen-derived reactive species, such as hydroxyl radical ((*)OH), whenever a suitable chemiluminescent probe is obtainable. Reported herein is the development of a rapid and specific method for detecting (*)OH production using a specific probe, indoxyl-beta-glucuronide (IBG), a low-level chemiluminescence emitter. Using the Fenton reagent as a source of (*)OH, it was shown that IBG could el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 29 publications
0
60
0
Order By: Relevance
“…26 Thiourea is an effective radical scavenger for • OH. 27 The inhibited CL signals were measured, respectively, after the addition of 20 µL of thiourea at different concentrations.…”
Section: Inhibition Effects Of Thioureamentioning
confidence: 99%
“…26 Thiourea is an effective radical scavenger for • OH. 27 The inhibited CL signals were measured, respectively, after the addition of 20 µL of thiourea at different concentrations.…”
Section: Inhibition Effects Of Thioureamentioning
confidence: 99%
“…Furthermore, CL is an effective method in research on ROS, because of the associated instantaneous nature of CL and the short lifetime of ROS radicals (11)(12)(13)(14)(15)(16). Goto et al (17) successfully investigated the CL mechanism of the alkalineearth metal peroxides (MgO 2 , BaO 2 ) with CL reagents (luminol and lucigenin), and demonstrated that the hydroxyl ( • OH) and • O 2 − were released chiefly on the MgO 2 and BaO 2 , respectively, with CL.…”
Section: Ros As Hydrogen Peroxide (H 2 O 2 ) Superoxide Anion ( • Omentioning
confidence: 99%
“…Among the oxygen-centred free radicals, •OH is considered to be one of the most potent oxidizers (13). Thiourea is an effective radical scavenger for •OH (25).…”
Section: Confirmation Of •Oh On Cao 2 By CLmentioning
confidence: 99%
“…Some tests rely on photometric measurements of the concentration of artificial radicals, which absorb light at a suitable wavelength or react with additional chromophores [15]. Other methods use the ability of antioxidants to reduce luminol chemiluminescence [16,17]. The antioxidantmodulated damage inflicted on biomolecules by radicals can also serve as a test of the antioxidative properties [20,21].…”
Section: Introductionmentioning
confidence: 99%